Оценка персонала как основной инструмент мотивации труда - Горощенко, В.В. (Стратегія і механізми регулювання промислового розвитку, 2016)
Обоснована необходимость оценки и мотивации персонала. Представлено определение мотивационного потенциала предприятия на основе выявления мотивационных потребностей работников и измерения степени удовлетворенности, выявленных потребностей по методике Ш. Ричи и Р. Мартина. Обґрунтовано необхідність оцінки і мотивації персоналу. Надано визначення мотиваційного потенціалу підприємства на основі виявлення мотиваційних потреб працівників та вимірювання ступеня задоволеності, виявлених потреб за методикою Ш. Річі та Р. Мартіна. Modernization of incentive mechanisms is a fairly effective direction in the development of personnel policy, since it allows improving the performance of organizations without significant expenditure of limited financial resources.Staff evaluation is a powerful tool for motivating work.Motivational potential of the enterprise includes motivated employees, focused on achieving the objectives of the enterprise.The definition of the motivational potential of the enterprise includes two stages: the first stage is the definition of the motivational needs of workers, the second is the measurement of the degree of satisfaction of the identified needs.To implement the assessment, the possibility of using such a tool, which is a motivational profile, is considered. To assess the motivational potential, the methods of R. Martin and S. Richie were applied, on the basis of which the research of the motivational potential of Novorossnab Ltd. employee was carried out.